Diagnosis of injuries of sciatic nerve and its branches - R. I. Khamzayev; V. P. Bersnev; Yu. I. Boroda; Ye. N. Zharova (Бюллетень сибирской медицины, 2008)
The results of examination and surgically treatment of 50 patients with sciatic nerve and branches lesions are presented in paper. Sciatic nerve and branches injury and degree of their damage is diagnosed, functional outcome were described, tactic and treatment recommendations were given in dependence to injury mechanisms, location, surgical techniques.